Strategi Pengembangan Produk Kuliner Di Pusat Kuliner Pratistha Harsa Purwokerto - Purnomo, Rochmat Aldy (Jurnal Ekonomi, 2016)
This study aims to analyze the development strategy Pratistha Harsa Culinary Market. Collecting data using the techniques of interview, observation and literature. The respondents were selected ie Pratistha Harsa Chief Manager, Chairman of the Society Pratistha Harsha, traders culinary Pratistha Harsa. The population of merchants in Pratistha Harsa number of 65 peoples and a sample of 40 seller respondents. Selection of the sample using simple random sampling. This research using SWOT Matrix and QSP Matrix. The results showed that the development strategy for the culinary center Pratistha Harsa obtained from the SWOT Matrix and Matrix QSP is using WT strategy, namely to minimize weaknesses and avoid external threats. It can be concluded that the formulation of the strategy of development of the culinary center Pratistha Harsha, looking at strengths, weaknesses, opportunities and threats of Pratistha Harsa relocation program that decision makers in Pratistha Harsha will apply Weaknesess-Threats Strategy.